NARASI SIMBOL DAN MAKNA PADA TEKS SAWERAN PERNIKAHAN DESA KADU GEDONG KABUPATEN PANDEGLANG BANTEN SEBAGAI UPAYA MEMPERKAYA BAHAN PEMBELAJARAN SASTRA DI SMP - Ilmi Solihat; Farid Ibnu Wahid (Jurnal Prasasti Ilmu, 2021)
This study was conducted to determine the functions and meanings contained in the traditional expression of the text of the Saweran wedding ceremony in Kadu Gedong Village, Pandeglang, Banten. The text studied is the kawih text, which will be analyzed with a semantic approach. The values of character education are also important points in this study, such as religious values, honesty, and tolerance in order to advance a person's basic potential to behave well and think positively, as well as develop the behavior of the nation's multicultural children. Furthermore, the results of the analysis of the narration of symbols and meanings in the Saweran text at the wedding ceremony in Kadu Gedong Village will be associated with existing competencies in junior high school, then a literary module, especially poetry learning, will be made. The results of the analysis show that first, the text of kawih saweran marriage has a function as a mandate to the bride and groom, and becomes a provision in the household, as well as a form of joy carried out by the two couples. Second, it has an inherent meaning, such as lexical meaning, direct meaning, figurative meaning, grammatical meaning, and cultural meaning. Third, it has character education values that are in accordance with the VII grade VII Junior High School learning implementation plan.